The Effect of Workload and Work Stress on Burnout: The Mediating Role of Work-Life Balance among BPKAD Employees in Palopo City - Wahyuni Tasya Ramadani; S. Saharuddin; J. Jusman (Manunggal Halim Jaya, 2026)
This study aims to examine the effect of workload and Work Stress on burnout, with work-life balance as a mediating variable among employees of the Regional Financial and Asset Management Agency of Palopo City. This study employs a quantitative approach using a survey method. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Work Stress has a positive and significant effect on burnout, while workload does not have a significant effect on burnout. Furthermore, workload has a positive and significant effect on work-life balance, whereas Work Stress does not significantly affect work-life balance. In addition, work-life balance is found to have a significant mediating role in the relationship between workload, Work Stress, and burnout. These findings suggest that managing Work Stress and maintaining work-life balance are essential in reducing employee burnout. This study provides practical implications for organizations, particularly in the public sector, to develop strategies that support employee well-being and performance.